2020
DOI: 10.7717/peerj.10053
|View full text |Cite
|
Sign up to set email alerts
|

Silicon flow from root to shoot in pepper: a comprehensive in silico analysis reveals a potential linkage between gene expression and hormone signaling that stimulates plant growth and metabolism

Abstract: Background Silicon (Si) is categorized as a quasi-essential element for plants thanks to the benefits on growth, development and metabolism in a hormetic manner. Si uptake is cooperatively mediated by Lsi1 and Lsi2. Nevertheless, Lsi channels have not yet been identified and characterized in pepper (Capsicum annuum), while genes involved in major physiological processes in pepper are Si-regulated. Furthermore, Si and phytohormones may act together in regulating plant growth, metabolism and tolerance against st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 110 publications
(159 reference statements)
0
7
0
1
Order By: Relevance
“…The major phytohormones upregulated by Si under abiotic stress conditions include ABA, JA, GA, ET, SA, BR, and IAA ( Arif et al, 2021 ). Si-induced phytohormones synergistically regulate the growth, metabolism, and stress tolerance in pepper, as shown by in silico data analysis ( Gómez-Merino et al, 2020 ). In tobacco and rice, Si regulates gene expression of plant hormones like ABA, JA, SA, and ETH to adjust metabolism against abiotic stress factors ( Table 1 ).…”
Section: Si-induced Differential Phytohormone Synthesis Under Abiotic...mentioning
confidence: 99%
“…The major phytohormones upregulated by Si under abiotic stress conditions include ABA, JA, GA, ET, SA, BR, and IAA ( Arif et al, 2021 ). Si-induced phytohormones synergistically regulate the growth, metabolism, and stress tolerance in pepper, as shown by in silico data analysis ( Gómez-Merino et al, 2020 ). In tobacco and rice, Si regulates gene expression of plant hormones like ABA, JA, SA, and ETH to adjust metabolism against abiotic stress factors ( Table 1 ).…”
Section: Si-induced Differential Phytohormone Synthesis Under Abiotic...mentioning
confidence: 99%
“…However, breeding methods and genetic control of Si uptake in wheat can be improved by adapting knowledge from other related cereal crops, particularly rice. Reportedly, Si uptake is a polygenic trait and its inheritance is conditioned by many minor genes (Gómez-Merino et al 2020). Also, the expression of Si uptake is highly affected by genotype by environment interactions, suggesting the need for multi-environmental selection of test genotypes to identify varieties that are efficient in Si uptake, and are high yielding and stable candidates for production or breeding.…”
Section: Breeding For Drought Tolerancementioning
confidence: 99%
“…Compared with traditional materials, nanomaterials have many advantages and are applied in the information industry, environmental industry, energy ( Zhao et al, 2018 ; Hao et al, 2021 ; Zhao et al, 2021 ) and environmental protection, biological medicine, and other fields ( Castiglione et al, 2011 ). The growth and development of plants are regulated by many factors, such as temperature and hormones ( Brandhoff et al, 2017 ; Ibañez et al, 2017 ; Kim et al, 2017 ; Sun et al, 2019 ; Gómez-Merino et al, 2020 ). An increasing number of studies have shown that nanomaterials also have an impact on the growth and development of plants ( Thuesombat et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%